Obesity Exacerbates Acute Gastrointestinal Injury and Intestinal Barrier Dysfunction in Early-Stage Acute Pancreatitis - Huang, Qing; Wu, Zhe; Zhang, Yuanyuan; Wu, Yun; Shi, Chenchen; Liu, Yulan (Turkish Journal of Gastroenterology, 2023)
Background: The impact of obesity on the severity of acute pancreatitis and subsequent acute gastrointestinal injury remains an important consideration. This study aimed to determine the clinical relationship between obesity and acute gastrointestinal injury in earlystage acute pancreatitis. Methods: This was a prospective study that enrolled 194 acute pancreatitis patients. Results: The median body mass index was 26.5 (7.0) kg/m2. Considering etiology of acute pancreatitis, 90 patients had gallstones, 48 had hypertriglyceridemia, 36 were alcohol users, and 20 were others. A total of 116 patients had mild acute pancreatitis and the rest had severe acute pancreatitis. The median of bedside index of severity in acute pancreatitis score was 1 (2) and the serum concentration of C-reactive protein was 80.5 (60.0) mg/L. Acute pancreatitis was accompanied by multiple organ dysfunction in 60 cases and by pancreatic necrosis in 34. A total of 52 patients were admitted to intensive care unit. The values of body mass index were higher in patients with severe acute pancreatitis than those with mild acute pancreatitis. A similar trend emerged in patients with hyperlipidemic acute pancreatitis compared to other causes. Body mass index had a positive relationship with bedside index of severity in acute pancreatitis scores. Noticeably, body mass index was statistically raised from gastrointestinal injury grade 1 to grade 4. The values of body mass index also showed relevance with intestinal barrier function evaluated by d-lactate, diamine oxidase, and intestinal fatty acid binding proteins. Furthermore, body mass indexes were statistically higher in patients having adverse outcomes of acute pancreatitis. Conclusion: This prospective study showed that obesity might contribute to increasing the severity of acute pancreatitis and aggravate subsequent intestinal injury in early-stage acute pancreatitis. Cite this article as: Huang Q, Wu Z, Zhang Y, Wu Y, Shi C, Liu Y. Obesity exacerbates acute gastrointestinal injury and intestinal barrier dysfunction in early-stage acute pancreatitis. Turk J Gastroenterol. 2023;34(4):421-426.